Peculiarities of a backstroke swimming technique acceleration in elementary education - Шейко, Лилия Викторовна (Slobozhanskyi Herald of Science and Sport, 2016)
Sheyko L. Purpose: to research the possibility of intensification and improvement of the efficiency of swimming training for adults by use of accelerated learning backstroke swimming techniques. Material & Methods: the study involved a total of 43 people aged 30–40 years. Applied: analysis and generalization of scientific and methodological literature; analysis of the learning process of swimming training for adults; development and approbation of an accelerated backstroke swimming technique on the base of the recreational sports complex LLC «Technocom» (Kharkiv, Author's swimming school of U. Blyzniuk), teacher observation, experiment. Results: a study shows that developing of swimming skills of people tested occurs faster and more effectively if the accelerated procedure is used. Backstroke swimming skill formation time for examinees: check group had 26 to 36 lessons, there were 25 to 32 exercises with and without use of supporting means; the experimental group had 12 to 24 lessons with use of 15 exercises without supporting means. Conclusions: as a result of the experiment, it was found that the use of the proposed accelerated training method allows to intensify backstroke swimming learning process for people aged 30–40, due to training course total duration reduction (2 times) and number of exercises used, and also allows to master quicker the main improving distance according to age of the engaged.